Demonic possession and exorcism in early modern England: Contemporary texts and their cultural contexts - Almond, Philip C (Cambridge University, 2013)
The first book devoted to demonic possession and exorcism in early modern England. Offers modernised versions of significant texts on nine cases of demonic possession from the period 1570 to 1650. The modernised texts are placed within the context of an Introduction to demonic possession in England across the period.